1989
DOI: 10.1016/0014-5793(89)80645-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of high‐ and low‐affinity epidermal growth factor receptors in human hepatoma cell lines

Abstract: Data are presented from a comparative research on expression of epidermal growth factor (EGF) receptors and response to EGF of six independently established cell lines derived from human hepatoma. These lines differ in terms of the degree of differentiation, presence of hepatitis B virus (HBV) DNA copies in integrated form and expression of HBV genes. Our results indicate differential expression of membrane EGF receptors and differential response to EGF under serumand hormone-free culture conditions. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…EGF-receptor protein is present in detergent extracts of Hep G2 cells [23], but the data reported here indicate that, under conventional culture conditions, only very low levels of surface 125I-EGF binding occur. This concurs with the observation that EGF binding to Hep G2 cells was the lowest observed among a panel of six hepatocellular carcinoma-derived cell lines [24], and the low level of binding of an anti-(EGF receptor) monoclonal antibody to this cell type [23]. However, after culture in the presence of 2% DMSO, EGF binding to Hep G2 cells is dramatically enhanced.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…EGF-receptor protein is present in detergent extracts of Hep G2 cells [23], but the data reported here indicate that, under conventional culture conditions, only very low levels of surface 125I-EGF binding occur. This concurs with the observation that EGF binding to Hep G2 cells was the lowest observed among a panel of six hepatocellular carcinoma-derived cell lines [24], and the low level of binding of an anti-(EGF receptor) monoclonal antibody to this cell type [23]. However, after culture in the presence of 2% DMSO, EGF binding to Hep G2 cells is dramatically enhanced.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the development of increased binding of EGF to Hep G2 cells, they did not develop a proliferative response to EGF, even after removal of DMSO. Under the conditions of culture used, however, in the absence of DMSO we have not found the low level of proliferation in response to EGF that some authors have reported [24] and, like others, we regard Hep G2 cells as being non-responsive to EGF [28]. The failure of EGF to modulate growth under conditions in which EGF binding is markedly enhanced and EGF-receptor down-regulation occurs confirms that proliferation in this tumour-derived cell line is not controlled by EGF-receptor-mediated stimulation.…”
Section: Discussioncontrasting
confidence: 77%
“…However, the degree of increase varied dramatically-4.6-fold in infected Huh7 cells, 2.7-fold in PLC, 1.8-fold in Hep3B, 1.4-fold in HA22T, and 1.2-fold in Chang live cells (Fig. The degree of cell differentiation is based on the production of plasma proteins and the levels of human leukocyte antigen class I antigen induced by interferon-␥ [Clementi et al, 1989]. …”
Section: Various Degrees Of Cytopathic Effects In the Five Liver Cellmentioning
confidence: 99%
“…Hepatitis B virus (HBV) DNA integration was detected in HA22T, PLC, and Hep3B cell lines, and HBV surface antigen was detected in PLC and Hep3B cells. By comparison, Chang liver is a non-tumorigenic but differentiated liver cell line (Table I) [Aden et al, 1979;Knowles et al, 1980;Clementi et al, 1987Clementi et al, , 1989Lin et al, 1995]. These cell lines were used to assess whether tumorigenic status and differentiation levels affect dengue virus replication.…”
Section: Dengue-2 Virus Infection and Different Replication Rates In mentioning
confidence: 99%
“…For example, some of these cell lines were highly tumorigenic when placed in vivo (Richardson et al, 1969;Knowles et al, 1980). In addition, while hepatocyte growth factor (HGF) and epidermal growth factor (EGF) were mitogenic for primary hepatocytes, HGF was reported to be cytostatic for the hepatoma cell lines HepG2, Hep3B, and H35 (Higashio and Shima, 1993), and EGF was inhibitory of the HA22T/VGH and Li7A hepatoma cell lines (Clementi et al, 1989). Finally, some human hepatoma cell lines also chronically produced hepatitis proteins (Aden et al, 1979).…”
Section: Introductionmentioning
confidence: 99%